Meningkatkan Ketahanan Pangan dengan Memanfaatkan Pekarangan Rumah - M. Ilham; Khairul Razak Mustofa; Ratu Suspita Sukman; Dea Ananda; Dinda Lestari; Rahmi Tri Jaya; Santri Sahar; Muhammad Fauzan; Safar Diknas L; Muh. Aswin M; Duta Nur Halisah (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Social changes and lifestyles of the elderly and children at the Al-Hikmah orphanage are very different from before living in the orphanage and after living in the orphanage. The purpose of this study was to see the extent of social changes and lifestyles of the elderly and children at the Al-Hikmah orphanage. The method used in this study is capacity building which aims to increase individual or group understanding of the problems they face while equipping them with ways to overcome them independently. The results of the analysis showed that there was a significant increase in the knowledge of the elderly about cholesterol and hypertension. Before the intervention, 40% of the elderly still did not understand the mpact of cholesterol and hypertension. The results of the analysis showed that there was a significant increase in children's knowledge about healthy lifestyles. As many as 30% of children at the Al-Hikmah orphanage still did not understand what a healthy lifestyle was